Renal and Glucose-Lowering Effects of Empagliflozin and Dapagliflozin in Different Chronic Kidney Disease Stages - Lin, Yi-Hsuan; Huang, Yu-Yao; Hsieh, Sheng-Hwu; Sun, Jui-Hung; Chen, Szu-Tah; Lin, Chia-Hung (Frontiers in Endocrinology, 2019)
Objective: The objective of this study was to investigate the effects of sodium-glucose cotransporter 2 (SGLT2) inhibitors on renal function in different stages of chronic kidney disease (CKD). Design and Methods: We conducted a retrospective cohort study using longitudinal claims data from May 2016–December 2017 from the Chang Gung Research Database. Patients who used one of the three types of SGLT2 inhibitor available at Chang Gung Memorial Hospital, namely empagliflozin 10 mg/tab (Empa10), empagliflozin 25 mg/tab (Empa25), and dapagliflozin 10 mg/tab (Dapa), were included, with the same number of matched non-users. Analysis of variance was used for continuous variables and the chi-square test was applied for categorical variables. Differences in data between two groups were analyzed using an independent t-test, and the basic data before and after treatment were analyzed using generalized estimating equation (GEE). The association among renal function changes was analyzed using a Cox proportional hazards model, with the results presented as unadjusted hazard ratios (HRs) with 95% confidence intervals (95% CIs). Results: Among the 7,624 SGLT2 inhibitor users, 1,696 patients used Empa10, 2,654 used Empa25, and 3,274 used Dapa. Compared with non-users, dapagliflozin had the lowest risk of estimated glomerular filtration rate (eGFR) decrease over 40% from baseline within 1 year (HR 0.36, 95% CI 0.25–0.51). By using the ICD-10-CM code N179, the acute kidney injury (AKI)-related hospitalization rate was lower in Empa10 and Dapa users than in non-users (HR 0.65, 95% CI 0.49–0.86). Conclusion: Lower risk of eGFR decrease over 40% and AKI-related hospitalization was found in all SGLT2 inhibitor users across the different CKD stages.